Metode Dakwah Perspektif Hadis: Telaah Hadis Salam - Shonhaji, Siti Qurrotul Aini (Fakultas Dakwah UIN KHAS Jember, 2023)
The hadith, which initially took the form of the sayings, character, behavior, and decisions of the Prophet Muhammad, has now transformed into a collection of writings or texts. This condition provides space for hadith scholars and researchers to re-examine according to their abilities in understanding the hadith. By studying the hadith, we can imitate and practice the words, actions, and decisions of Prophet Muhammad. Emulating and practicing the teachings of Muhammad is part of the form of da'wah. Therefore, it is important to study the hadith of Muhammad in order to know the Prophet's methods of da'wah. This research is a qualitative library research. The theory used to analyze the collected data is the thematic theory (hadith maudhu'i). The result of this study is that Muhammad is a role model who serves as the reference point for Islamic teachings, as an explanation of the Qur'an. After the Prophet's death, this reference point was replaced by the hadith of the Prophet, which contains the implementation of Islamic teachings. These hadiths are taught and practiced by religious leaders (da'is) as the guardians and successors of Islamic teachings. In carrying out their mission as da'is, religious leaders use two methods, namely the method of speech and the method of wisdom. These two methods are found in the hadith about spreading greetings. The hadith emphasizes direct practice, both orally and with wisdom. Without practice, the spreading of greetings commanded by the Prophet will not be carried out. In addition, the greeting hadith contains the element of uniting the community because the greeting is the best chain of prayers for the listener and an expression of love and care from the speaker.